A study on consumer adoption towards the mobile shopping application for online shopping among generation-Y /cAmirul Ashraf Mohamad Rozi - Amirul Ashraf Mohamad Rozi, 1995-, author; Norzaidahwati Zaidin; Azman Hashim International Business School (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2019